Taxes, High-Income Executives, and the Perils of Revenue Estimation in the New Economy - Goolsbee, Austan (American Economic Review, 2000)
This paper attempts to help explain the unforecasted, excess' personal income tax revenues of the last several years. Using panel data on executive compensation in the 1990s, it argues that because the gains on most stock options are treated as ordinary income for tax purposes, rising stock market valuations are directly tied to non-capital gains income. This blurred line between capital and wage income for has affected tax revenue in three ways, at least for these high-income people. First, stock performance has directly affected the amount of ordinary income that people report by influencing their stock option exercise decisions. Second, the presence of options gives executives more flexibility in changing the timing of their reported income and appears to make them much more sensitive to the short-run timing of tax changes, even accounting for the stock market changes of the period. Third, because of the tax rules on options, changing the capital gains tax rate, as the U.S. did in the late 1990s, can lead individuals to exercise their options early to convert the expected future gains into lower-taxed forms. The data show significant evidence of each of these effects and in all three cases, executives working in the new' economy and high-technology sectors(This abstract was borrowed from another version of this item.)